Advanced Community College ESL Composition An Integrated Skills Approach - Perez, Edgar; Behseta, Sara; Rae, Jenell (Open textbook library., 2020)
This book has been created to provide a framework for building your skills in writing and critical thinking. It provides access to published samples from professional authors along with essay drafts from ESL students who have polished their skills in their respective writing courses. The themes in the readings will give you a variety of topics to discuss with your classmates, which may inspire your own deeper thinking and writing. Overall, we hope that as you proceed through these chapters, you will build confidence and develop your voice in the classroom and beyond. Welcome to the world of academic writing!